ESTIMATE PARAMETERS AND RELIABILITY FUNCTION FOR TRUNCATED LOGISTIC DISTRIBUTION: SIMULATION STUDY - Salih, Makki Akram Muhamed; Taqi, Ahmed Yassin (MAGISTRA, 2015)
We study In this search the two parameters truncated logistic distribution , and we derived· Probability density function (p.d.f)· Cumulative distribution function (c.d.f)· Reliability function R(x)· Hazard function h(x) For truncated logistic distribution with estimate two parameters and reliability function by Weightedleast square method and Maximum likelihood method.Keywords: Logistic Distribution, Truncation Logistic Distribution